2010
DOI: 10.4097/kjae.2010.58.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of propofol and pentobarbital on hydrogen peroxide-stimulated hepatic SNU761 cells

Abstract: BackgroundPropofol and barbiturates are both known to protect cells of several organs against ischemia/reperfusion injury, but there are few reports on any possible protective effects on human hepatocytes. We investigated the activities of both agents on human hepatic SNU761 cells under hydrogen peroxide (H2O2)-induced oxidative stress.MethodsTo determine whether propofol and pentobarbital protect hepatocytes from H2O2-induced toxicity, we used SNU761 cells, a human hepatocellular carcinoma (HCC) cell line. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Although Shimono et al, [16], found no evidence for a beneficial effect of propofol against liver hypoxia/reoxygenation injury in rat liver slices, propofol was shown to protect suspensions of isolated rat hepatocytes from an oxidant insult [12]. Moreover, Lee et al, [34], found that propofol, but not pentobarbital, exerts a protective effect on hepatocytes exposed to H 2 O 2 oxidant stress in vitro. Reasons for these discrepancies may include the use of different experimental models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Shimono et al, [16], found no evidence for a beneficial effect of propofol against liver hypoxia/reoxygenation injury in rat liver slices, propofol was shown to protect suspensions of isolated rat hepatocytes from an oxidant insult [12]. Moreover, Lee et al, [34], found that propofol, but not pentobarbital, exerts a protective effect on hepatocytes exposed to H 2 O 2 oxidant stress in vitro. Reasons for these discrepancies may include the use of different experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has shown that propofol increased hepatic blood flow in a dose dependent manner [35], the hepatoprotective effect of propofol may be also dose-dependent. Lee et al, [34], found that propofol has a protective effect on hepatocytes in a clinically relevant concentrations of 1-50 M, because peak plasma concentrations of propofol are reportedly 40-60 M (7.12-10.68 g/mL) at anesthesia induction and 10-25 M (1.78-4.45 g/mL) during anesthesia maintenance [42]. de la Cruz et al, [13], reported that 50-300 M, but not 10 M, propofol had significant effects on all the oxidative-stress variables they studied in rat brain slices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that the benefits of nutrient interventions seen in oxidative stress resistance may extend from cancer prevention to therapeutic intervention [92,93]. A series of recent studies by Longo et al have shown that fasting can selectively protect healthy cells while sensitizing tumor cells to drug treatment.…”
Section: Introdcutionmentioning
confidence: 99%
“…[26] Moreover, previous studies confirmed that propofol has a hepatoprotective effect through its role in reduction of free radical generation and free radical scavenging, dumping of inflammatory reactions. [32,33] It has inhibitory effects on calcium channels and diminution of intracellular calcium overload , improved microcirculation through reported induced nitric oxide (NO) and vasodilatory prostanoid production. [33,34] ROC curves revealed that miR-122 had the highest efficiency in prediction of ischemia/reperfusion injury followed by miR-223.…”
Section: Discussionmentioning
confidence: 99%
“…[32,33] It has inhibitory effects on calcium channels and diminution of intracellular calcium overload , improved microcirculation through reported induced nitric oxide (NO) and vasodilatory prostanoid production. [33,34] ROC curves revealed that miR-122 had the highest efficiency in prediction of ischemia/reperfusion injury followed by miR-223. These findings suggested that estimation of plasma miR-122 and miR-223 in CHC undertaking anesthesia could be an early, and reliable biomarker for predicting I/R liver injury.…”
Section: Discussionmentioning
confidence: 99%